Penyuluhan dan Pendampingan Literasi Jajanan Halal dan Toyyib di Madrasah Kota Padang - Milya Sari; Media Roza; Nurhasnah Nurhasnah; Awida Awida; Asri Atuz Zeky (Institut Agama Islam Negeri Bengkulu, 2022)
This community service aims to provide counseling and literacy assistance for halal snacks and thoyyib for MIN, MTsN, and MAN students in the city of Padang, as well as form a halal community among madrasah students. The selection and targeting of this training was based on research findings on the quality of snacks for madrasah students in the city of Padang. Many snacks are not feasible / unsafe for consumption. Service activities are carried out in three stages. The first stage is preparation, coordinating with the Madrasah and LPPOM MUI West Sumatra, surveying the location of the service implementation, determining the location of the service, and preparing technical training and instruments. The second stage is implementation, through counseling and mentoring activities that are carried out on an ongoing basis. The third stage is completion, analyzing the data obtained and evaluating and making reports. The results of the training activities indicate that counseling and mentoring activities can increase the literacy of halal snacks and thoyyib madrasah students. This can be seen from the posttest scores and participants' perceptions of counseling and mentoring. The results were very good and the participants gave a positive response to the counseling and assistance provided